Psychological Resilience And Its Relationship To Attentional Control And Performance Of Students' Volleyball Preparation Skill - Naji Hussein, Hasanain (International Journal of Psychosocial Rehabilitation, 2020)
The current study was conducted in order to identify the relationship of psychological resilience with attentional control and the performance of the skill of preparing volleyball for students, as the researcher used the descriptive method in the manner of correlational relations. For the academic year 2018-2019, the aim of the research is to identify psychological resilience, attentional control, and the performance of the preparation skill in volleyball for students, to identify the relationship of psychological flexibility with attentional control, and the performance of the skill of repeating volleyball for students. Attention and testing the performance of the preparation skill in volleyball, which is within the curriculum for the students of the first stage for students of the Department of Physical Education and Sports Sciences, College of Basic Education.